Control strategies for energy management system in electric vehicle using high-level supervisory control - Abulifa, Abdulhadi Abdulsalam; Che Soh, Azura; Hassan, Mohd Khair; Raja Ahmad, Raja Mohd Kamil; Mohd Radzi, Mohd Amran (Scientific Research Archives, 2022)
Energy Management System (EMS) is a computer-supported device utilized by drivers of electrical frameworks to maintain management and to optimize the efficiency of transmission systems. In this paper, a control strategy for EMS using on the High-level Supervisory Control (HLSC) has been reviewed. This HLSC strategy with an intelligent management algorithm technique has been evolving rapidly particularly in EMS for Electrical Vehicles (EVs). Their revolutionary applications provide efficient control strategies for EMS that increase capabilities, efficiency and accuracy, as well as reducing energy consumption in EVs. Applying EMS with HLSC control strategy with an intelligent management algorithm that is able reallocate the electrical power flow inside the EVs system to boost power efficiency and obtain optimum effectiveness. Such innovative solutions can enhance the efficiency of smart EMS in EVs as the future sustainable transportation.